Peranan Pastoral Konseling dalam Pemulihan Kedukaan Bagi Jemaat yang Ditinggalkan oleh Pasangannya - Jonny Samuel; Leo Runesi (Sekolah Tinggi Theologia Ebenhaezer Tanjung Enim, 2026)
The loss of a spouse is a traumatic event that affects the emotional, social, spiritual, and economic aspects of the bereaved individual. This study aims to analyze the role of pastoral counseling in supporting grief recovery among church members who have lost their spouses, particularly in the post–COVID-19 context. The main issue addressed is the lack of a holistic pastoral approach that integrates psychological, spiritual, and socio-economic dimensions. Using a descriptive qualitative method, data were collected through observation, in-depth interviews, and literature review to understand the emotional experiences of congregants and the effectiveness of church pastoral care. The pastoral approach is based on Kübler-Ross’s five stages of grief, Worden’s four tasks of mourning, Pargament’s concept of religious coping, and Sen’s Capability Approach for economic empowerment. The results indicate that pastoral counseling combining healing and empowering dimensions effectively enhances emotional recovery, strengthens faith, restores social function, and promotes financial independence among grieving congregants. Evaluation using the Five Dimensions of Pastoral Care model demonstrates significant improvement across emotional, spiritual, social, economic, and community support aspects. The study concludes that a comprehensive and sustainable pastoral strategy is essential to accompany bereaved church members through their grief and help them rebuild a meaningful and holistic life.